2014
DOI: 10.4081/jlimnol.2014.569
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the ability of Daphnia galeata resting egg production in Lake Biwa

Abstract: The Daphnia galeata population in Lake Biwa (Japan)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Caution is needed, however, when reconstructing past Daphnia populations using resting eggs. Firstly, abundance of resting eggs stored in lake sediments may not reflect population density of Daphnia species in the past because the production rate of resting eggs depends on not only environmental conditions [ 16 , 17 ] but also the population genetic structures [ 18 , 19 ]. Thus, for estimating population density in the past, it is essential to quantify remains of planktonic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Caution is needed, however, when reconstructing past Daphnia populations using resting eggs. Firstly, abundance of resting eggs stored in lake sediments may not reflect population density of Daphnia species in the past because the production rate of resting eggs depends on not only environmental conditions [ 16 , 17 ] but also the population genetic structures [ 18 , 19 ]. Thus, for estimating population density in the past, it is essential to quantify remains of planktonic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Since both JPN1 and JPN2 genotypes are obligately asexual, they can produce dormant eggs without males. However, the rate of dormant egg production may differ between these genotypes as shown in previous studies of Daphnia species (Roulin et al., 2015; Tsugeki & Urabe, 2014). Indeed, our laboratory experiment showed that the rate of dormant egg production was higher in the JPN2 genotype than in the JPN1 genotype.…”
Section: Discussionmentioning
confidence: 83%